The Role and Function of the Aceh Baitul Mal in Increasing the Economic Growth of the Acehnese Indigenous People - Junaedi, I Wayan Ruspendi; Damayana, I Wayan; Waruwu, Dermawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to describe and analyze the role and function of the Aceh Baitul Mal in increasing the economic growth of the Acehnese. The results show that Baitul Mal Aceh is a non-structural regional institution that has the authority to manage and develop zakat, waqf, religious assets to benefit the people, as well as being the guardian of the supervisor of orphans and/or asset managers. an inheritance that does not have a guardian based on Islamic Sharia becomes an institution that has formed a new service system in sharia-based financial management and empowerment. The BaitulMal Institute collects zakat, infaq, alms, and waqf as a source of finance by optimizing the value of muzakki, manfiq, and muwafiq. Besides, the presence of Baitul Mal Aceh is also very instrumental in shaping empowerment services through optimal ziswaf sources. The role of BaitulMal has received support from all levels of Aceh's Indigenous Peoples, this is because Baitul Mal is present to greatly assist the lower class community and provide solutions to economic problems to those who have the right without charging interest or the like on the community in developing their economy. Baitulmal financial resources have never experienced a deficit financially.